2003
DOI: 10.1210/jc.2002-020369
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Pulsatility Is Disrupted at a Threshold of Energy Availability in Regularly Menstruating Women

Abstract: To investigate the dependence of LH pulsatility on energy availability (dietary energy intake minus exercise energy expenditure), we measured LH pulsatility after manipulating the energy availability of 29 regularly menstruating, habitually sedentary, young women of normal body composition for 5 d in the early follicular phase. Subjects expended 15 kcal/kg of lean body mass (LBM) per day in supervised exercise at 70% of aerobic capacity while consuming a clinical dietary product to set energy availability at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
566
6
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(610 citation statements)
references
References 44 publications
25
566
6
13
Order By: Relevance
“…Low energy availability, but not the stress of exercise alone, suppressed leptin rhythm (27) and altered LH pulsatility (26) in eumenorrheic, sedentary women. Similarly, 72-h fasting disrupted follicle growth and lengthened the follicular phase in lean women with body fat Ͻ20% (24), but not in normal-weight women with body fat similar to that of our subjects (Ϸ27%) (25).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Low energy availability, but not the stress of exercise alone, suppressed leptin rhythm (27) and altered LH pulsatility (26) in eumenorrheic, sedentary women. Similarly, 72-h fasting disrupted follicle growth and lengthened the follicular phase in lean women with body fat Ͻ20% (24), but not in normal-weight women with body fat similar to that of our subjects (Ϸ27%) (25).…”
Section: Discussionmentioning
confidence: 89%
“…It has been suggested that LH pulsatility is disrupted at a threshold of energy availability deep in negative energy balance (26). Low energy availability, but not the stress of exercise alone, suppressed leptin rhythm (27) and altered LH pulsatility (26) in eumenorrheic, sedentary women.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low energy availability can be attained through low caloric intake, high exercise energy expenditure or a combination of both. Well-controlled laboratory experiments have demonstrated that an energy availability below 30 kcal · kg −1 fat-free mass (FFM) · day −1 is associated with the suppression of key metabolic hormones, such as leptin, insulin, insulin-like growth factor 1 (IGF-1) and triiodothyronine (T3) (Hilton & Loucks, 2000;Loucks & Heath, 1994;Loucks & Thuma, 2003;Loucks et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that controlled experiments on the metabolic effects of low energy availability have only been conducted in sedentary women (Hilton & Loucks, 2000;Ihle & Loucks, 2004;Loucks & Heath, 1994;Loucks & Thuma, 2003;Loucks et al, 1998); no controlled experiments have utilized men, and particularly exercising men. Reductions in T3, IGF-1 and testosterone have been reported in field studies in male soldiers exposed to various levels of energy deficiency during military training (Friedl et al, 2000;Kyrolainen et al, 2008;Nindl et al, 2007), which suggests that key metabolic hormones may also be suppressed in severely energy-deficient exercising men.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of endurance sports (marathon, triathlon) their daily requirements may be as high as 4000 kcal/day. On the other hand, Loucks et al [33] proved that an energy availability (defined as the energy intake minus the energy expenditure) of 30 kcal/kg LBM/day is a threshold value below which the reproductive function is depressed due to disturbances in the LH pulsatility and amplitude. Moreover, Williams et al [62] demonstrated that the frequency of menstrual disturbances is markedly affected by the magnitude of the daily energy deficit, and is significantly greater for a 42% than for an 8% energy deficiency.…”
Section: Energy Availability In Female Athletesmentioning
confidence: 99%